Clinical researchEpidural spinal cord stimulation in therapy-resistant angina pectoris – influence on myocardial perfusion or improvement of the quality of life? Pilot study - Dyrla, Wioletta; Kuch, Marek; Barczewska, Monika; Kostana, Liliana; Czubalska, Magdalena; Maksymowicz, Wojciech; Dąbrowski, Marek; Dłużniewski, Mirosław (Archives of Medical Science, 2008)
Introduction: Epidural spinal cord stimulation (SCS) seems to be an alternative treatment for therapy-resistant angina pectoris. This report assesses the efficacy of SCS in improving quality of life (QoL) and influence on myocardial perfusion. Material and methods: In the year 2004 seven patients with therapy-resistant angina pectoris were enrolled in a prospective study. The patients had a spinal cord stimulator implanted. Myocardial perfusion was evaluated in SPECT-MIBI prior to implantation and in the 3rd, 6th and 12th month after. Coronary reserve was assessed in an exercise test and QoL in a questionnaire. Results: QoL improved in all patients within 3 months of the implantation. Coronary capacity increased in 2 patients and in 5 patients it stayed at the same level. Myocardial perfusion improved in 2 patients, deteriorated in 3 patients and in 2 it did not change. Conclusions: SCS improves QoL. It seems not to influence myocardial perfusion.